Babygirl [videorecording (Blu-Ray)] - Reijn, Halina, 1975-; Kidman, Nicole, 1967-; Dickinson, Harris, 1996-; Banderas, Antonio; Wilde, Sophie, 1997-; McGregor, Esther; Reilly, Vaughan; Slezak, Victor, 1957-; Silva, Leslie, 1968-; Jansen, Gaite, 1991- (A24 Films, 2025)
A high-powered CEO puts her career and family on the line when she begins a torrid affair with her much younger intern, where the balance of power is constantly shifting.